Near hanging with Multiple Tentative Cuts: A Case Series (Medico Legal Update, 2024)
Suicide is one of the major global health issues specially in countries having low to medium socioeconomic condition. Hanging is method of choice for adults to commit suicide. Near hanging defined as person who survive a hanging injury for enough time to reach hospital. Tentative cut or self-inflicted injury is an intentional and direct injury to own’s body part. It is also known as self-harm, self-wounding, moderate self-mutilation and parasuicide. Various factors responsible for high mortality in near hanging are low systolic blood pressure (15, Glassgow coma scale (GCS)